2016
DOI: 10.1063/1.4943630
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of plasma properties during gas-condensation of Cu nanoparticles

Abstract: Since the mean, standard deviation, and modality of nanoparticle size distributions can vary greatly between similar input conditions (e.g., power and gas flow rate), plasma diagnostics were carried out in situ using a double-sided, planar Langmuir probe to determine the effect the plasma has on the heating of clusters and their final size distributions. The formation of Cu nanoparticles was analyzed using cluster-plasma physics, which relates the processes of condensation and evaporation to internal plasma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…43 However, the processes of NP formation and growth inside a GAS have never been assessed by in-flight imaging techniques, although indirect analyses by Langmuir probe measurements have recently been reported. 44,45 In this work, we aimed at the SAXS analysis of the formation and growth of copper NPs inside a GAS in situ, both in close vicinity and at remote distances from the magnetron.…”
Section: Introductionmentioning
confidence: 99%
“…43 However, the processes of NP formation and growth inside a GAS have never been assessed by in-flight imaging techniques, although indirect analyses by Langmuir probe measurements have recently been reported. 44,45 In this work, we aimed at the SAXS analysis of the formation and growth of copper NPs inside a GAS in situ, both in close vicinity and at remote distances from the magnetron.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the preparation of high-quality copper-oxide NPs with a narrow size distribution are of increasing interest in fields such as solar energy conversion cells or catalysis 24 , 25 . Cu based NPs have been previously produced using gas aggregation sources, either for fundamental studies concerning the fabrication process itself 26 , 27 , or for testing new cluster sources 28 . However, to our knowledge, an accurate control of the Cu oxidation state through reactive sputtering using gas aggregation sources that avoid poisoning of the target has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…4 where it was observed that they can form at the surface of the Cu NW and then deposit onto a substrate directly beneath the Cu NW. By using the EDX signal from Cu, the sizes of such NCs were estimated to have a bi-modal distribution which has been already associated with characteristic nucleation and growth mechanisms described in the literature 12,41 .…”
Section: Discussionmentioning
confidence: 96%
“…A recent application of nanomaterials involves miniaturisation of electronic circuits and devices which has potential to revolutionise the electronics industry [7][8][9][10][11][12] , not only by extending the validity of Moore's law, but exceeding the scientific vision beyond it [13][14][15] . In this context, the search for reliable synthesis and processing routes for nanomaterials remains a significant challenge for academia and technology companies: for example, the ion-beam-induced processing doping of semiconductor nanowires was shown to severely degrade them via mechanisms known as ion-induced bending 16,17 .…”
Section: Introductionmentioning
confidence: 99%